PENGARUH KUAT ARUS PADA PENGELASAN PADUAN ALUMINIUM 6061 DENGAN MENGGUNAKAN METODE LAS TIG TERHADAP KEKERASAN DAN STRUKTUR MIKRO - Rochim Toat Wicaksono; Suharno Suharno; Budi Harjanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
The objective of research was to find out the effect of current on microstructure and hardness value in Aluminium Alloy 6061 before (raw material) and after welding using Tungsten Inert Gas (TIG) welding method with filler rod ER4043. This research uses experiment methods. Technique of analyzing data used was a descriptive comparative research. The instruments used for testing microstructure and hardness were Olympus Metallurgical Microscope and Vikers Hardness Tester. Base on the result of research, it could be concluded that the result of microstructure testing showed the reduced Mg2Si phase width after welding. In raw material, the Mg2Si phase seemed to diffuse surrounding the α-Al phase surface, but the result of welding using TIG welding method with current of I00 A, 110 A, and 115A showed that Mg2Si phase reduced in each specimen, so that α-Al phase was very dominant. The hardness value of hardness result showed the different hardness level. The specimen with current of 110A had higher hardness level of 65.4 VHN than the specimen with current of 100 A (55.7 VHN) and 115 A (55.9 VHN). The result of hardness testing on raw material was 120.4 VHN. This research showed that the welding using varying current changed microstructure and affected the hardness value of Aluminum Alloy 6061.